1999
DOI: 10.1002/(sici)1097-4628(19990222)71:8<1267::aid-app7>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

X-ray diffraction characterization of the structure of zein-Oleic acid films

Abstract: Wide-angle (WAXS) and small-angle X-ray scattering (SAXS) studies of dry granular zein, zein fibers, zein-oleic acid resin, and zein-oleic acid films are reported. WAXS patterns showed two diffuse rings for these samples indicative of noncrystalline structures. Measured d-spacings of ϳ 4.6 Å and ϳ 10.5 Å were found for zein-oleic acid resins and films, consistent with the presence of ␣-helical segments. The granular zein and zein fibers had ϳ 4.6-Å and ϳ 9.5-Å spacings. Neither the films nor the fibers showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
62
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(73 citation statements)
references
References 35 publications
9
62
0
2
Order By: Relevance
“…Their diameter varied from 20 to 1,000 nm. The formation of periodic structures of zein and oleic acid was reported by Lai et al 11 The assembly of zein-oleic acid structures involved both hydrophobic interactions and hydrogen bonds as described by Wang et al 10 Properties of zein and oleic acid films were described in past reports where oleic acid improved zein film flexibility and decreased Young's modulus. 16,17 Fig.…”
Section: Effect Of Amphiphilic Compoundsmentioning
confidence: 88%
“…Their diameter varied from 20 to 1,000 nm. The formation of periodic structures of zein and oleic acid was reported by Lai et al 11 The assembly of zein-oleic acid structures involved both hydrophobic interactions and hydrogen bonds as described by Wang et al 10 Properties of zein and oleic acid films were described in past reports where oleic acid improved zein film flexibility and decreased Young's modulus. 16,17 Fig.…”
Section: Effect Of Amphiphilic Compoundsmentioning
confidence: 88%
“…Dados referentes a soluções, nas quais filmes com estruturas homogêneas são conseguidas, indicam concentrações entre 10 a 34 g.L -1 para os quais propriedades mecânicas semelhantes as aqui apresentadas são registradas [32,33] . De forma similar, adições maiores que 2,0% de AO como plastificante não tem levado a melhoras significativas nas propriedades mecânicas de filmes de zeínas [34] . Avaliações de altas concentrações de plastificantes indicam que estes também contribuem para a formação de estruturas heterogêneas com separação de fases entre as proteínas e o plastificante [13,30] .…”
Section: A 1000 Sequência Complexa De Picos Devidos Principalmente Asunclassified
“…Neste caso a hidratação é facilitada considerando que este tipo de organização conduz a orientação dos componentes polares em direção à superfície [40] . Análises cristalográficas confirmam a formação de bicamadas [32] ou entrelaçadas de AO quando elevadas concentrações são adicionados às zeínas [34] . Outro aspecto observado e registrado em publicação prévia [14] , é que após os primeiros segundos de contato da gota com a superfície, há um comportamento de recuo do ângulo medido com tendência a estabilização após aproximadamente alguns minutos.…”
Section: A 1000 Sequência Complexa De Picos Devidos Principalmente Asunclassified
“…Resin-drawn films can be made by dispersing zein with the plasticizer oleic acid in aqueous alcohol and precipitating out the resin in cold water (Lai et al 1999). These authors proposed a model for such a zein resin-drawn film, based on their own x-ray data and molecular measurements determined by Matsushima et al (1997).…”
Section: Films and Coatingsmentioning
confidence: 99%
“…These authors proposed a model for such a zein resin-drawn film, based on their own x-ray data and molecular measurements determined by Matsushima et al (1997). Lai et al (1999) suggested that the oleic acid adsorbed onto the charged residues on the zein surface by electrostatic forces.…”
Section: Films and Coatingsmentioning
confidence: 99%